Highly‐efficient optically transparent planarized transmit‐arrays using heterogeneous unit cells - Yangbin Jiang; Xin Yu Wu; Zhi Hao Jiang; Longzhu Cai; Wei Hong (Electronics Letters, 2023)
Abstract Two K‐band optically‐transparent (OT) transmit‐arrays (TAs) are proposed and demonstrated, which realize pencil beam and flat‐top beam, respectively. Based on the equivalent circuit analysis approach, the TA unit cells are designed using cascaded low‐loss cyclic olefin copolymer substrates and transparent conductor films with a 360° phase shifting and a total panel thickness of 0.46λ0. Phase compensation and an intersection approach are utilized to synthesize the pencil beam TA, with an aperture efficiency of 39.2%, and flat‐top beam TA, respectively. Both TAs are fabricated and characterized, showing a good agreement between the simulated and measured results. The pencil beam TA achieves a peak gain of 31.8 dBi with an 1‐dB gain bandwidth of 6.5%, while the flat‐top beam TA realizes a peak gain of 20.3 dBi with an 1.8‐dB beamwidth of 13°. The verified OT TAs can be useful candidates for communication and satellite applications in the 5G millimetre‐wave band.